2016
DOI: 10.3390/diseases4040038
|View full text |Cite
|
Sign up to set email alerts
|

Serum Wisteria Floribunda Agglutinin-Positive Mac-2 Binding Protein Could Not Always Predict Early Cirrhosis in Non-Viral Liver Diseases

Abstract: Background: Wisteria floribunda agglutinin-positive human Mac-2-binding protein (WFA(+)-M2BP) is a novel non-invasive marker of liver fibrosis. The goal of the study was to investigate whether the novel serum biomarker WFA(+)-M2BP or other non-invasive markers are useful for the prediction of liver fibrosis in patients with nonalcoholic steatohepatitis (NASH), autoimmune hepatitis (AIH), and primary biliary cholangitis (PBC). Methods: We examined a significant correlation between serum WFA(+)-M2BP levels and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Serum WFA(+)-M2BP was measured using an HISCL M2BPGi assay kit (Sysmex Co., Kobe, Japan) [ 17 ]. The aspartate aminotransferase (AST) to alanine aminotransferase (ALT) ratio (AAR) was calculated using the following equation: AAR = AST/ALT.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Serum WFA(+)-M2BP was measured using an HISCL M2BPGi assay kit (Sysmex Co., Kobe, Japan) [ 17 ]. The aspartate aminotransferase (AST) to alanine aminotransferase (ALT) ratio (AAR) was calculated using the following equation: AAR = AST/ALT.…”
Section: Methodsmentioning
confidence: 99%
“…Wisteria floribunda agglutinin-positive Mac-2 binding protein [WFA(+)-M2BP] is a newly recognized fibrosis marker that was developed as a marker for HCV infection in Japan [ 16 , 17 ]. M2BP is a heavily N-glycosylated glycoprotein and is secreted as a ligand of galectin-3 (Mac-2) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 86 In fact, both these biomarkers were only able to identify extensive fibrosis, but as another study has shown, there is considerable overlap with earlier fibrotic stages. 87 …”
Section: Markers For Fibrosismentioning
confidence: 99%
“…Furthermore, the WFA + -M2BP levels were positively correlated with levels of AST and ALT, which are markers of liver inflammation. These results suggest that WFA + -M2BP levels are increased in patients with hepatic functional reserve deterioration or severe inflammation; histological analysis was not performed in this study (Haga et al 2016;Nishikawa et al 2016;Ishii et al 2017).…”
Section: Discussionmentioning
confidence: 80%